Enhancing local support for tidal energy projects in developing countries: Case study in Flores Timur Regency, Indonesia. Issue 4 (13th July 2020) - Ramachandran, Rohit; Takagi, Ken; Matsuda, Hirotaka
Abstract: Tidal energy is a new renewable energy source that can be used to provide electricity to remote islands, while contributing to climate change mitigation. Like all renewable energy projects, public awareness and support are not only crucial for the successful development of marine renewable energy projects too, but also aid the private sector project developers in making long‐term plans. As information about tidal energy is not easily available, public views toward it are not well known, making it challenging for the project developers to strategize implementation strategies. Moreover, the limited studies focusing on such social aspects of tidal energy come from advanced countries, highlighting the lack of focus on cases from developing countries. Our study fulfills this gap by providing a case study focusing on the social aspects of tidal energy in a developing country, which can be utilized by developers for designing their public engagement strategies. We estimate the public support for tidal energy in eastern Indonesia using two methods: (a) stages of development and (b) information provision. Using the first method, we found that support for tidal energy is lower in the initial stages, but it keeps rising once the public can realize the benefits. The second method shows that though people tend to support tidal energy, the role of information provision is dissimilar compared with western cases. Additionally, Probit modeling shows that Age, Education, Collective Outcome Favorability, and especially, Individual Outcome Favorability are the key factors that positively impact the support for tidal energy in eastern Indonesia.